(untitled) (American Journal of Islam and Society, 2017)
This article provides an annotated translation of a treatise written by the famous scholar Jalal al-Din al-Suyuti (d. 911/1505) in defense of the hadiths condemning sodomy (liwāṭ). The article situates such a defense within the current discourse on Islam and homosexuality, summarizing the main arguments for and against the prohibition of liwāṭ as well as how the “traditionalist” and "Progressive” camps have constructed their arguments.This article provides an annotated translation of a treatise written by the famous scholar Jalal al-Din al-Suyuti (d. 911/1505) in defense of the hadiths condemning sodomy (liwāṭ). The article situates such a defense within the current discourse on Islam and homosexuality, summarizing the main arguments for and against the prohibition of liwāṭ as well as how the “traditionalist” and "Progressive” camps have constructed their arguments.